Factors Influencing Compliance with Triple Elimination Examination - Aryani, Roza; Muna, Sirajul; Elyza, Elyza (Indonesian Journal of Global Health Research, 2024)
The impact of non-compliance by pregnant women in carrying out triple elimination examinations is the cause of increasing high risk rates in pregnant women (bleeding, infectious diseases, etc.). Knowledge, attitudes, beliefs, beliefs, perceptions and traditions are important components as predisposing factors for health behavior. The triple elimination examination is intended to help reduce the fairly high maternal mortality rate in Indonesia. Objective to conduct an analysis of factors influencing compliance with triple elimination examinations in the Krueng Sabee Community Health Center Work Area, Aceh Jaya Regency in 2023. This quantitative research has a cross sectional design. The population of this study was all pregnant women with a gestational age of more than 20 weeks. Total sampling technique was used in this research (30 people). Data collection for this research was carried out by distributing questionnaires that had been tested for validity (> 0.361) and reliability (0.801). Data analysis used the chi square test. Shows that there is an influence between maternal knowledge (p=0.000), maternal attitude (p=0.009) and husband's support (p=0.001) on triple elimination examination. There is an influence of husband's knowledge, attitudes and support on triple elimination examinations in the Krueng Sabee Community Health Center Work Area, Aceh Jaya Regency.